2006
DOI: 10.1002/chem.200600208
|View full text |Cite
|
Sign up to set email alerts
|

Assembly of Nanotubes of Poly(4‐vinylpyridine) and Poly(acrylic acid) through Hydrogen Bonding

Abstract: Nanotubes of poly(4-vinylpyridine) (PVP) and poly(acrylic acid) (PAA) were fabricated by hydrogen bonding based on layer-by-layer (LbL) assembly. The uniform and flexible tubular structures were characterized by scanning electron microscopy (SEM) and transmission electron microscopy (TEM). FTIR and X-ray photoelectron spectroscopy (XPS) measurements confirm the formation of hydrogen bonds in the assembled nanotubes. PAA can be released from the assembled PAA/PVP nanotubes in a basic aqueous solution to give th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 33 publications
1
50
0
Order By: Relevance
“…For example, the formation of hydrogen bonds between hydroxyl groups of poly(acrylic acid) and the nitrogen groups of poly(4-vinylpyridine) was exploited to coat the pore walls of PC membranes with multilayer structures consisting of these polyelectrolytes [246]. An advantage of this approach lies in the fact that solutions in organic solvents can be used to deposit the monolayers.…”
Section: Multilayer Nanotubes By Layer-by-layer Depositionmentioning
confidence: 99%
“…For example, the formation of hydrogen bonds between hydroxyl groups of poly(acrylic acid) and the nitrogen groups of poly(4-vinylpyridine) was exploited to coat the pore walls of PC membranes with multilayer structures consisting of these polyelectrolytes [246]. An advantage of this approach lies in the fact that solutions in organic solvents can be used to deposit the monolayers.…”
Section: Multilayer Nanotubes By Layer-by-layer Depositionmentioning
confidence: 99%
“…Sequential assembly of polymers within a controlled pore followed by template removal can result in self-standing tubular structures. Li et al reported fabrication of microtubes based on hydrogen-bonding LbL self-assembly from poly(acrylic acid) (PAA) and PVP [226]. They also demonstrated successful removal of the PAA and the resulting porous walled tubes could also be useful as carriers in drug delivery or as catalyst supports.…”
Section: Progress On Fundamental Aspectsmentioning
confidence: 96%
“…[22][23][24][25] These LbL-assembled composite nanotubes have been fabricated by applying a variety of assembly components including natural or synthetic polyelectrolytes, inorganic nanoparticles, dyes, dendrimers, peptides, DNA, and enzymes. The driving force for multilayer assembly has also been extended from the electrostatic interactions of the polymer chains to other non-electrostatic interactions including hydrogen bonding, [26] DNA hybridization, [27] and covalent bonding. [28] Therefore, the availability of a wide-range of organic or inorganic components, the variety of interactions, and the versatility in assembly approaches spectacularly enables one to introduce a high degree of multifunctionality within these LbL-assembled nanotubes.…”
Section: Introductionmentioning
confidence: 99%